Perspective on fibrinolytic therapy in COVID-19: the potential of inhalation therapy against suppressed-fibrinolytic-type DIC - Asakura, Hidesaku (J Intensive Care, 2020)
A high rate of thrombotic complications, such as pulmonary embolism, has been linked to mortality in COVID-19, and appropriate treatment of thrombosis is important for lifesaving. Although heparin is frequently used to treat thrombotic pathology in COVID-19, pulmonary embolism is still seen in severe cases. Although systemic fibrinolytic therapy is a focus of attention because a thrombotic pathology is the cause of death in severe COVID-19, it should be kept in mind that fibrinolytic therapy might be harmful at advanced stage of COVID-19 where the status of disseminated intravascular coagulation (DIC) has been transmitted from suppressed-fibrinolytic to enhanced-fibrinolytic in disease progression of COVID-19. In this respect, inhalation therapy with fibrinolytic substances might be a safe and promising treatment.